2019
DOI: 10.3233/ch-170311
|View full text |Cite
|
Sign up to set email alerts
|

The expression of hSR-B1 on platelets of patients with coronary artery disease (CAD)

Abstract: Taken together, the results of the present study raise the possibility that the measurement of hSR-B1 expression on human platelets may provide a valuable insight that reflects the status of RCT in patients with atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In this study, following co-culture of monocytes with platelets, we investigated the mRNA expression of CD36 , scavenger receptor class A (SRA) , and acyl-coenzyme A cholesterol acyltransferase (ACAT) in monocytes, which are among the key genes in lipid accumulation [22,23]. We also evaluated the gene expression changes that are expected to enhance the cholesterol efflux from foam cells, including ATP-binding cassette transporter A1 (ABCA1) , ATP-binding cassette transporter G1 (ABCG1) , peroxisome proliferator-activated receptor γ (PPAR γ) , liver X receptor-α (LXR- α ) , and scavenger receptor class B (SRB) [24,25,26]. Our results showed that platelets elevated the expression of mRNA of CD36, ACAT, ABCA1, SRB, and LXR- α.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, following co-culture of monocytes with platelets, we investigated the mRNA expression of CD36 , scavenger receptor class A (SRA) , and acyl-coenzyme A cholesterol acyltransferase (ACAT) in monocytes, which are among the key genes in lipid accumulation [22,23]. We also evaluated the gene expression changes that are expected to enhance the cholesterol efflux from foam cells, including ATP-binding cassette transporter A1 (ABCA1) , ATP-binding cassette transporter G1 (ABCG1) , peroxisome proliferator-activated receptor γ (PPAR γ) , liver X receptor-α (LXR- α ) , and scavenger receptor class B (SRB) [24,25,26]. Our results showed that platelets elevated the expression of mRNA of CD36, ACAT, ABCA1, SRB, and LXR- α.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple lines of evidence indicated that CD36 and ACAT pave the way for the formation of foam cells through enhancing the capability of the cells to uptake platelets/ox-LDL and cholesterol esterification, respectively [22,23]. On the other hand, increased expression levels of SRB, LXR-α, and ABCA1 were also reported to be associated with the cholesterol efflux from macrophage foam cells [24,25,26]. Other studies also showed that the gene expression of proteins such as CD36, ACAT1, LXR-α, and ABCA1 are increased during macrophage-derived foam cell formation [22,23,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, following co-culture of monocytes with platelets, we investigated the mRNA expression of CD36, scavenger receptor class A (SRA), and acyl-coenzyme A cholesterol acyltransferase (ACAT) in monocytes, which are among the key genes in lipid accumulation [22,23]. We also evaluated the gene expression changes that are expected to enhance the cholesterol efflux from foam cells, including ATP-binding cassette transporter A1 (ABCA1), ATP-binding cassette transporter G1 (ABCG1), peroxisome proliferator-activated receptor γ (PPARγ), liver X receptor-α (LXR-α), and scavenger receptor class B (SRB) [24,25,26]. Our results showed that platelets elevated the expression of mRNA of CD36, ACAT, ABCA1, SRB, and LXR-α.…”
Section: Platelets Induced the Expression Of The Genes Involved In Chmentioning
confidence: 99%